PEMANFAATAN AMPAS TEBU SEBAGAI MATERIAL ADSORBEN BESI, MANGAN, pH, COD, BOD DAN TSS PADA AIR SUMUR - Rina Rina; Alimuddin Alimuddin; Aman Sentosa Panggabean (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2019)
The research about adsorption concentration of iron, manganese, pH, COD, BOD and TSS at well water using baggase as adsorbent material. The content of iron and manganese was determined using AAS; pH using pH meter; COD and BOD using titration method; TSS using gravimetry me. The results of research showed the best percentage of decrease was use of baggase activated with KOH, can be showed in the reduction of iron was 42.80%, manganese 94.93%, pH 8.45%, COD 24.75%, BOD 32.21%, TSS 2.88%, the percentage of recovery of iron 98.05% and manganese 88.31%.